Detection of CD16low Neutrophil Subpopulations - Riera Cervantes, Norma Edith (2003)
The analysis with a three-color staining procedure using anti-CD49d/anti-CD16/anti-CD45 monoclonal antibodies is useful to detect CD16low neutrophil subpopulation. Patients with aplastic anemia and neutropenia tend to have low expresion of CD16 on neutrophils as consecuence of a increased apoptosis or the presence of Paroxismal Nocturnal Hemoglobinuria clon. The aim of this sudy was to seek a cytometric strategy to evaluate this subpopulation.